Microstructure and reactivity of cryomilled Al-Ni energetic material with nanoscale lamellar structure - Sharma, Ashutosh; Lee, Hansung; Ahn, Byungmin (Journal of Materials Science, 2022)
An Al-Ni alloy system with excellent energy density and mechanical performance is regarded as a novel high-energy–density material to enhance the energy emission of explosives or propellants. In this study, we explored the influence of a process control agent (PCA) varying from 0, 0.1, 0.25, 0.5, to 1.0 (wt.%) on the cryomilling of Al and Ni powder mixtures. The structural and morphological evolution of cryomilled Al-Ni powder was determined by X-ray diffraction, scanning electron microscopy, particle size distribution analysis, and transmission electron microscopy. Differential thermal analysis was used to study the exothermic reaction temperature, and activation energy calculations were performed using Kissinger plots. The results indicated that the addition of PCA changed the Al-Ni aggregate shape from oval to granular. The lamellar size also became finer after adding PCA up to 0.25 wt.% but the lamellar shape changed to granular at 1 wt.% PCA. These nanoscale lamellae serve as nuclei to produce Al-Ni reaction compounds, which gradually decrease the activation energy. The optimal concentration of PCA was determined to be 0.25 wt.% as this concentration decreased the activation energy of the Al-Ni alloy because of the fine, homogeneous, and alternate Al-Ni lamellae in the alloy when cryomilled.
Keywords: Al powder; Cryomilling; Energy density; Energy emissions; High energy density materials; Mechanical performance; Nano scale; Ni powder; Powder mixtures; Process control agents